Quantitative and qualitative evaluation of the use of nonsteroidal anti-inflammatory drugs in the Russian Federation over 10 years - G. I. Syraeva; A. S. Kolbin; S. A. Mishinova; A. A. Kalyapin (Izdatelstvo OKI, 2022)
Relevance. Studies devoted to the assessment of consumption, as well as to the issues of pharmacosafety of nonsteroidal anti-inflammatory drugs, are limited at the national level in the Russian Federation. The study of these issues will determine the general trends of consumption and prescription of this group of drugs.Aim. To assess the consumption pattern of NSAIDs in the Russian Federation in the period from 2010 to 2020.Methods. Information was searched using data from the state register of drugs (GRLS) as well as national database downloads (automated information system of Roszdravnadzor; AIS RZN). To estimate the consumption of the main INN from the group of NSAIDs for the period 2010-2020 the information on the sales volume of all trade names, sold for sale in the Russian Federation was unloaded from the database of IQVIA Solutions Ltd. and analyzed.Results. The analysis showed that the first place by total amount of consumption was occupied by acetylsalicylic acid (5 953 058 854); second place - paracetamol (4 635 122 085); third place - ibuprofen (3 230 415 088); fourth place - metamizole (4 172 344 008); fifth place - ketorolac (91 617 809,04); sixth - nimesulide (69 761 7481,8). The claimed INNs showed a slightly different distribution when calculating the DDDs/P (patient-year) totals, namely, in descending order, nimesulide, ketorolac, ibuprofen, acetylsalicylic acid, paracetamol, and methamisole.Conclusion. The indicated levels of consumption do not correlate with the data of the national database "Pharmacovigilance", which indicates insufficient post-marketing monitoring of the safety profiles of the indicated medicines.